European energy and transport and GHG emissions. Trends to 2050. Reference scenario 2013 - Capros, P.; De Vita, A.; Hoeglund Isaksson, Lena; Winiwarter, W.; Purohit, P.; Bottcher, H.; Frank, S.; Havlik, Petr; Gusti, M; Witzke, HP. (Luxembourg, 2014)
"This report is an update and extension of the previous trend scenarios for development of energy systems taking account of transport and GHG emissions developments. The publication presents the new 'EU reference scenario 2013', finalised in July 2013. It focuses even more than previous ones on the energy, transport and climate dimensions of EU developments and the various interactions among policies, including now also specific sections on emission trends not related to energy. Its time horizon has been extended up to 2050. It reports for the first time on EU28 including Croatia"